Pencapaian Sustainibilitas Organisasi Melalui Kualitas Kehidupan Kerja - Zumaroh, Zumaroh; Kusumawati, Diah Ayu (Studi Ekonomi dan Kebijakan Publik, 2024)
Purpose: This study aimed to analyze the factors of organizational desire through achieving quality of work life and job satisfaction in optimizing human resource performance at PT. Kawasan Industri Wijayakusuma Semarang. Methodology/approach: This study used a qualitative method with data acquisition through questionnaires and census sampling to determine the number of respondents. Data management used SPSS 25 software with simple and multiple linear regression analysis methods, t-test, coefficient of determination, and Sobel test. Results/findings: The results of this study indicate that quality of work life and job satisfaction affect employee performance. Furthermore, job satisfaction plays an important role as a mediator in the relationship between quality of work life and employee performance. Conclusion: Quality of work life significantly improves employee performance, both directly and indirectly, through job satisfaction as a mediating variable at PT Kawasan Industri Wijayakusuma. Limitations: This study has limitations, namely, using only one sample of companies/organizations and two factors as variables to measure human resource performance in achieving business desires. Contribution: This study has a contribution, namely it can be useful for organizations in emitting quality of work life, job satisfaction, and how to improve human resource performance to achieve business desires.